Analisis efektifitas penerapan Critical Path Method (CPM) pada proyek pembangunan tanggul Kali Lamong Kabupaten Gresik - Qordhowi, Andrian Firdaus Yusuf Al; Fendrawan, Rafi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
On construction projects, time and cost are very important and are one measure of success, along with budget and quality. Schedule the project to complete it quickly and efficiently. Critical Path Method (CPM) is a project planning and control method used to identify the most critical or crucial sequence of activities in a project. By determining the critical path, the project manager can know which activities have a very limited time tolerance so that they cannot be delayed without affecting the overall project schedule. The results of the analysis of the Microsoft Project 2019 application show that there are 13 critical work units. After analyzing the acceleration of duration using the method of additional overtime working hours and rescheduling using Microsoft Project 2019, the time comparison was found as follows: Work duration for the original Lamong River embankment construction item 295 days increased to 245 working days after the additional hours (crashing) with a total cost of Rp. 15,137,716,928.72 The percentage of time efficiency after the crashing was 16.95% with a duration difference of 50 working days. The cost efficiency percentage after accelerating with additional hours is 0.05% with a cost difference of Rp. 775,106,996.72.